(untitled) (Fiep Bulletin - online, 2019)
Oral breathing is a set of signs and symptoms that leads to a change in breathing pattern child. This modification leads tomorphological changes throughout the body, causing mandibular retraction, hypotonia of facial muscles, changes in ventilatorymechanics and postural deviation across the end. A posture change proprioception lead to changes in sensitivity and rebalancingof the muscle, favoring the repositioning of the head and cervical spine, increasing the airspace and favoring air flow. Physicaltherapy can help improve the quality of life of oral breather, as preventive and corrective actions. The breathing pattern implieschanges in orofacial structure and dynamics throughout the body, a nasal breathing improves airflow, reducing ventilatory musclestrength, avoiding repetition of respiratory infections as well as improving the tone of the face muscles. The posture correctionaids in modifying the structures of oral cervical spine alignment. This study is applied nature with a qualitative approach andexploratory objective through a literature reviewdeveloped from already prepared material, consisting mainly of books andscientific articles.